WITHDRAWN: Effect of Different Methods of Training in Body Composition and Lipid Profile in Occupational Men - Zin, Marjiana Angela; da Costa, Gisele Maria Tonin; Zaar, Andrigo (International Journal of Sport Studies for Health, 2017)
Withdrawn